PENGARUH PEMBELAJARAN DARING TERHADAP CAPAIAN HASIL BELAJAR SISWA SEKOLAH DASAR - Yeni Nora Fridayanti (PREMIERE : Journal of Islamic Elementary Education, 2021)
This study aims to determine the effect of online learning on the learning outcomes of elementary school students. The research method is carried out through library research by collecting data information related to relevant matters from various sources such as journals, articles, news, books. The criteria for selecting documents, namely that there is a discussion of online learning and the learning outcomes obtained during online learning in elementary schools. The results showed that online learning had an influence on student learning outcomes. This is caused by internal and external factors from students. Elementary school age students are at the concrete operational stage where they are able to do logical reasoning for things that are concrete in nature, while for things that are abstract in nature they are still unable to do it. Students have certain characteristics so they need time to adapt to be able to adjust to online learning. The learning outcomes obtained by students depend on how students respond to the online learning that is being carried out. The role of teachers and parents is very important for the success of students in learning.